Knowledge Creation in Strategic Alliance: Case of ‘Child Business’ Learning from ‘Parent Partner’ - Mansor, Zuraina Dato; Abdullah, Wan Mohamed Tarmizi Wan (The South East Asian Journal of Management, 2012)
-